A novel inhibitor of inducible NOS dimerization protects against cytokine‐induced rat beta cell dysfunction. (14th July 2018) - Zhong, Linlin; Tran, Tuan; Baguley, Tyler D; Lee, Sang Jun; Henke, Adam; To, Andrew; Li, Sijia; Yu, Shan; Grieco, Fabio A; Roland, Jason; Schultz, Peter G; Eizirik, Decio L; et al.
Abstract : Background and Purpose: Beta cell apoptosis is a major feature of type 1 diabetes, and pro‐inflammatory cytokines are key drivers of the deterioration of beta cell mass through induction of apoptosis. Mitochondrial stress plays a critical role in mediating apoptosis by releasing cytochrome C into the cytoplasm, directly activating caspase‐9 and its downstream signalling cascade. We aimed to identify new compounds that protect beta cells from cytokine‐induced activation of the intrinsic (mitochondrial) pathway of apoptosis. Experimental Approach: Diabetogenic media, composed of IL‐1β, IFN‐γ and high glucose, were used to induce mitochondrial stress in rat insulin‐producing INS1E cells, and a high‐content image‐based screen of small molecule modulators of Casp9 pathway was performed. Key Results: A novel small molecule, ATV399, was identified from a high‐content image‐based screen for compounds that inhibit cleaved caspase‐9 activation and subsequent beta cell apoptosis induced by a combination of IL‐1β, IFN‐γ and high glucose, which together mimic the pathogenic diabetic milieu. Through medicinal chemistry optimization, potency was markedly improved (6–30 fold), with reduced inhibitory effects on CYP3A4. Improved analogues, such as CAT639, improved beta cell viability and insulin secretion in cytokine‐treated rat insulin‐producing INS1E cells and primary dispersed islet cells. Mechanistically, CAT639 reduced the production of NO by allosterically inhibiting dimerization of inducible NOS (iNOS) without affecting its mRNA levels. Conclusion and Implications: Taken together, these studies demonstrate a successful phenotypic screening campaign resulting in identification of an inhibitor of iNOS dimerization that protects beta cell viability and function through modulation of mitochondrial stress induced by cytokines.